Multielemental composition and nutritional value of "dumosa" (Ilex dumosa), "yerba mate" (I. paraguariensis) and their commercial mixture in different forms of use - Maiocchi, Marcos Gabriel (2016)
Fil: Maiocchi, Marcos Gabriel. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.